Noncovalent Integration of a Bioinspired Ni Catalyst to Graphene Acid for Reversible Electrocatalytic Hydrogen Oxidation - Reuillard, Bertrand; Blanco, Matías; Calvillo, Laura; Coutard, Nathan; Ghedjatti, Ahmed; Chenevier, Pascale; Agnoli, Stefano; Otyepka, Michal; Granozzi, Gaetano; Artero, Vincent (ACS applied materials & interfaces, 2020)
Efficient heterogeneous catalysis of hydrogen oxidation reaction (HOR) by platinum group metal (PGM)-free catalysts in proton-exchange membrane (PEM) fuel cells represents a significant challenge toward the development of a sustainable hydrogen economy. Here, we show that graphene acid (GA) can be used as an electrode scaffold for the noncovalent immobilization of a bioinspired nickel bis-diphosphine HOR catalyst. The highly functionalized structure of this material and optimization of the electrode-catalyst assembly sets new benchmark electrocatalytic performances for heterogeneous molecular HOR, with current densities above 30 mA cm-2 at 0.4 V versus reversible hydrogen electrode in acidic aqueous conditions and at room temperature. This study also shows the great potential of GA for catalyst loading improvement and porosity management within nanostructured electrodes toward achieving high current densities with a noble-metal free molecular catalyst.
Keywords: bio-inspired catalysis; molecular HOR; non-covalent catalyst immobilization; PGM-free fuel cells; graphenic acid; molecular electrocatalysis